2013
DOI: 10.1111/dsu.12335
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes for Malignant Melanoma of the Face Treated Using Mohs Micrographic Surgery and Wide Local Excision

Abstract: Mohs micrographic surgery has oncologic outcomes of local recurrence, distant recurrence and overall survival similar to those of WLE for invasive facial melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 45 publications
1
31
0
1
Order By: Relevance
“…Although no prospective randomized trials have been performed to investigate whether MMS is more effective than WLE, the currently available data attest to the value and advantages of MMS for the treatment of MM. 9,[15][16][17] In a retrospective review of 151 patients with facial invasive melanoma, Chin-Lenn et al 16 reported no significant differences in disease-specific 5-year survival in patients who underwent WLE and those with lesions resected with MMS (83% in WLE vs. 92% in MMS; P = 0Á59). Similarly, an analysis by Trofymenko et al 9 of 43 443 patients with melanoma revealed comparable melanoma-specific mortality or OS outcomes in patients who underwent MMS and those who received other surgical modalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no prospective randomized trials have been performed to investigate whether MMS is more effective than WLE, the currently available data attest to the value and advantages of MMS for the treatment of MM. 9,[15][16][17] In a retrospective review of 151 patients with facial invasive melanoma, Chin-Lenn et al 16 reported no significant differences in disease-specific 5-year survival in patients who underwent WLE and those with lesions resected with MMS (83% in WLE vs. 92% in MMS; P = 0Á59). Similarly, an analysis by Trofymenko et al 9 of 43 443 patients with melanoma revealed comparable melanoma-specific mortality or OS outcomes in patients who underwent MMS and those who received other surgical modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Although no prospective randomized trials have been performed to investigate whether MMS is more effective than WLE, the currently available data attest to the value and advantages of MMS for the treatment of MM . In a retrospective review of 151 patients with facial invasive melanoma, Chin‐Lenn et al . reported no significant differences in disease‐specific 5‐year survival in patients who underwent WLE and those with lesions resected with MMS (83% in WLE vs. 92% in MMS; P = 0·59).…”
Section: Discussionmentioning
confidence: 99%
“…However, recurrence rates were 1.9% for MMS compared to 5.9% for WLE. Chin‐Lenn et al studied surgical outcomes of facial malignant melanoma treated by MMS (60 cases) compared with WLE (91 cases). They found no significant difference in 5‐year local recurrence rates, regional or systemic recurrence, nor disease‐specific survival.…”
Section: Discussionmentioning
confidence: 99%
“…Survival rates at 5-, 10, and 15-year follow-up were similar between WLE versus MMS groups for MIS ( Low recurrence rates <2% have been reported in the use of MMS for MIS and melanoma in a number of studies. [11][12][13][14][15][16][17][18] which allows for tissue preservation. Given that maximal amount of normal skin is preserved and the smallest surgical defect possible is obtained with MMS, it should be considered when lesions are located in areas of anatomical and cosmetic significance.…”
Section: Survival Outcomesmentioning
confidence: 99%
“…In this issue of Dermatologic Surgery , Chin‐Lenn and colleagues describe the outcomes of patients with invasive melanoma of the face treated using Mohs micrographic surgery (MMS) versus wide local excision over a 10‐year period. Although patient cohorts were notably different, a limitation of the retrospective nature of the study, outcomes of the treated groups were similar with respect to local, regional, and systemic recurrence and disease‐specific survival.…”
mentioning
confidence: 99%